Advanced material evaluations and considerations for electrostatic control in electronic device manufacturing - Chakkaew, Anusorn; Suriya-Amaranont, Chaba; Titiroongruang, Wisut (My University, 2013)
Electrostatic potential and electrostatic discharge (ESD) has been a manufacturing issue for years, not only limited to semiconductor-based electronic devices, hard dish drive assemblies, but also to adjacent electronic device manufacturing such as microelectromechanical systems and nanoelectromechanical systems devices. This research presents a complete material testing and evaluations for electrostatic control in electronic device manufacturing. There are materials and system evaluations and considerations of electrostatic generation on personnel, personnel grounding through wrist strap and grounding wire, personnel grounding through constant wrist strap monitor, and with static control footwear and floorings. This research also presents machine grounding measurement and consideration with ground impedance, when ground noise is present, area where most regular ohm meter fails. Discharge simulation from device handling materials, and electrostatic discharge characterization of static control surfaces for small and light devices. © 2013 American Scientific Publishers All rights reserved.
Keywords: Electrostatic discharge; ESD; Human body model; Human body voltage; Personal grounding